Cyclodextrin Based Nanoparticles for Drug Delivery and Theranostics - Dipak Dilip Gadade; Sanjay Sudhakar Pekamwar (Tabriz University of Medical Sciences, 2020)
Colloidal nanoparticulate technology has been described in the literature as a versatile drug delivery system. But it possesses some inherent lacunae in their formulation. Cyclodextrins (CDs) have been extensively reported for the solubility enhancement of poorly water-soluble drugs. The CDs can cause intervention in aspects related to nanoparticles (NPs) that include improving drug loading in nano-system, improving stability, site-specific/targeted drug delivery, improving solubility profile and absorption of the drug in nanosystem with consequent improvement in bioavailability, with the possibility of controlled release, safety and efficacy. They find application in for simultaneous diagnosis and therapeutics for better treatment procedures. The current communication is focused on the application of CDs to overcome troubles in nanoparticulate formulation and enhancement of their performance. It also envisages the theranostic aspects of CDs.